Prevotella species in the human gut is primarily comprised of Prevotella copri, Prevotella stercorea and related lineages - Yeoh, Yun Kit; Sun, Yang; Ip, Lawrence Yuk Ting; Wang, Lan; Chan, Francis K. L.; Miao, Yinglei; Ng, Siew C. (Scientific reports, 2022)
Prevotella species in the human gut microbiome are primarily comprised of Prevotella copri , and its diversity and function were recently investigated in detail. Much less is known about other Prevotella species in the human gut. Here, we examined the composition of Prevotella species in human guts by mapping publicly available gut metagenomes to a dereplicated set of metagenome-assembled genomes (MAGs) representing Prevotella lineages found in human guts. In most human cohorts, P. copri is the most relatively abundant species (e.g. up to 14.3% relative abundance in Tangshan, China). However, more than half of the metagenome reads in several cohorts mapped to Prevotella MAGs representing P. stercorea and several other species sister to P. stercorea and P. copri . Analyses of genes encoded in these genomes indicated that P. stercorea and related lineages lacked many hemicellulose degrading enzymes and were thus less likely to metabolise hemicelluloses compared with P. copri and copri-related lineages. Instead, P. stercorea genomes possess several carbohydrate esterases that may be involved in releasing ester modifications from carbohydrates to facilitate their degradation. These findings reveal unexplored Prevotella diversity in the human gut and indicate possible niche partitions among these related species.